2019
DOI: 10.1016/j.ejmp.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mouthpiece fixation devices for head and neck radiotherapy patients fabricated in PolyJet photopolymer by a 3D printer

Abstract: The purpose of our study was to evaluate the usefulness of a biocompatible class VI resin PolyJet photopolymer Objet MED610 (MED610)-made mouthpiece fabricated using a 3D printer as a fixation device for head and neck radiotherapy patients. Methods: Five mouthpieces made of GC Exafine putty type (GCEP) were fabricated from five dry skull bones. After computed tomography reconstruction of the GCEP-made mouthpiece and its surface extraction, the MED610-made mouthpieces were replicated. The sizes of the GCEP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…According to different origins of HNC, depressors or elevators were used to reduce incidental exposure of the tongue and healthy structures during RT [20]. These kinds of 3D printed bite blocks were manufactured recently, and their clinical use is still being investigated and evaluated [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…According to different origins of HNC, depressors or elevators were used to reduce incidental exposure of the tongue and healthy structures during RT [20]. These kinds of 3D printed bite blocks were manufactured recently, and their clinical use is still being investigated and evaluated [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the experimental study of the synthesized samples demonstrated high sound absorption efficiency. Kitamori et al [17] developed a biocompatible class VI resin polyjet photopolymer mouthpiece using polyjet printing, which was used as a fixation device for head and neck radiotherapy patients. Hong et al [18] developed a computer tomography (CT) image-based 3D-printed model of thyroid cancer using various kinds of 3D printers including polyjet printers and compared their accuracies and other aspects regarding facilitating this patient-physician communication.…”
Section: Polyjet Printingmentioning
confidence: 99%
“…A significant decrease in radiation dose to the tongue was demonstrated using 3D-printed devices (10). Kitamori et al suggested advantages of 3D-printed TRDs in terms of dose distribution with reduction of the integral dose to the surrounding normal tissue (11). Additionally, scattered radiation by dental restorative metals might be effectively absorbed by 3D-printing resin (11).…”
Section: Introductionmentioning
confidence: 99%
“…Given an adequate design, 3D-printed TRDs might support the accurate interfractional patient setup by using the remaining dentition for a rigid inter-jaw fixation, thus providing a defined position of the lower jaw in relation to the upper jaw. This might reduce longitudinal deviations in maxillomandibular relation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%